An Empirical Study of Labor Market Equilibrium Under Working Hours Constraints - Dunn, L. F. (The Review of Economics and Statistics, 1990)
Predictions of economic theory for the equilibrium condition of workers in three labor markets with differing working hours constraints are tested. Original data allow the marginal rate of substitution of income for leisure to be estimated directly. In two markets, working hours constraints resulting from high fixed employment costs and the overtime premium, respectively, cause workers to desire fewer and more hours. In the third market (agricultural labor), constraint factors are absent. The predicted relationship between the wage and the marginal rate of substitution of income for leisure holds in each case. Implications for agency and human capital models are investigated. Additionally, in the agricultural case, preferences and equilibria are indistinguishable for legal and illegal workers. Copyright 1990 by MIT Press.